The Representation of Multicultural Values in English Textbook for Economic Study: A Discourse Analysis - Widyarini, Puput; Mahmud, Murni; Abdullah, Abdullah (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
This study aimed to find the representation of multicultural values that contained in English for Business Studies, a Course for Business Studies and Economic Students by Ian Mac Kenzie. This research was conducted by using qualitative methods with a phenomenological approach. The researcher conducted discourse analysis for the content of the book, such as the data from the extract that was written in the book, the record from listening section and visual representation on the book. The book fulfilled the regulations from physics to the content. Multicultural values from selected textbooks are categorized by using Chaos framework. There are four kinds of them, appreciating other people's perspectives (AOPP), act of appreciating women's equal rights (AWER), respecting other people's traditions (ROPT) and act of appreciating other people's cultural products (AOPCP). In multicultural values, the book represented the multicultural values from Europe, South Africa, India, and Asia. Even though there are some gaps between the cultures, this book is still worth using. Keywords: Book, Multicultural Values, Standard.